Inappropriate prescribing in older fallers presenting to an Irish emergency department. - Kenny, Rose; Mc Mahon, Christine (My University, 2014)
BACKGROUND: certain medications increase falls risk in older people. OBJECTIVE: to assess if prescribing modification occurs in older falls presenting to an emergency department (ED). DESIGN: before-and-after design: presentation to ED with a fall as the index event. SUBJECTS: over 70's who presented to ED with a fall over a 4-year period. METHODS: dispensed medication in the 12 months pre- and post-fall was identified using a primary care reimbursement services pharmacy claims database. Screening Tool of Older Person's PIP (STOPP) and Beers prescribing criteria were applied to identify potentially inappropriate prescribing (PIP). Polypharmacy was defined as four or more regular medicines. Psychotropic medication was identified using the WHO Anatomical Therapeutic Chemical classification system. Changes in prescribing were compared using McNemar's test (significance P < 0.05). RESULTS: One thousand sixteen patients were eligible for analysis; 53.1% had at least one STOPP criteria pre-fall with no change post-fall (53.7%, P = 0.64). Beers criteria were identified in 44.0% pre-fall, with no change post-fall (41.5%, P = 0.125). The most significant individual indicators to change were neuroleptics, which decreased from 17.5 to 14.7% (P = 0.02) and long-acting benzodiazepines decreased from 10.7 to 8.6% (P = 0.005). Polypharmacy was observed in 63% and was strongly predictive of PIP, OR 4.0 (95% CI 3.0, 5.32). A high prevalence of psychotropic medication was identified pre-fall: anxiolytics (15.7%), antidepressants (26%), hypnosedatives (30%). New initiation of anxiolytics and hypnosedatives occurred in 9-15%, respectively, post-fall. CONCLUSION: a significant prevalence of PIP was observed in older fallers presenting to the ED. No substantial improvements in PIP occurred in the 12 months post-fall, suggesting the need for focused intervention studies to be undertaken in this area.
PUBLISHED
Keywords: potentially inappropriate prescribing; falls; older people; Ageing; Neuroscience